2005
DOI: 10.1186/1471-244x-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with personality disorders seen at an ordinary psychiatric outpatient clinic

Abstract: Background: Epidemiological studies have found reduced health-related quality of life (QoL) in patients with personality disorders (PDs), but few clinical studies have examined QoL in PDs, and none of them are from an ordinary psychiatric outpatient clinic (POC). We wanted to examine QoL in patients with PDs seen at a POC, to explore the associations of QoL with established psychiatric measures, and to evaluate QoL as an outcome measure in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
(21 reference statements)
4
28
1
3
Order By: Relevance
“…Two studies 119,121 investigated the known-group validity of the SF-36 and two studies 96,122,123 investigated this property in the SF-12. One study 119 investigated the responsiveness and convergent validity of the SF-36.…”
Section: Bipolar Disordermentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies 119,121 investigated the known-group validity of the SF-36 and two studies 96,122,123 investigated this property in the SF-12. One study 119 investigated the responsiveness and convergent validity of the SF-36.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Studies were undertaken in four countries. Nine 96,[119][120][121][122][123][124][125][126][127][128] of the 10 studies presented data for different personality disorders together. One study looked exclusively at individuals with borderline personality disorder.…”
Section: Bipolar Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the internal factors, personality seems to play a substantial role with respect to QOL or related concepts, such as life satisfaction and well-being (Larsen and Buss, 2005). Narud et al (2005) examined QOL in a sample of psychiatric outpatients with personality disorders of whom 75% had at least one co-morbid Axis-I disorder (according to DSM-IV classification). They found that patients with personality disorders have globally poor QOL compared to age-and gender-adjusted norm data.…”
Section: Introductionmentioning
confidence: 99%